Pengaruh Disiplin Dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT. Mandala Multifinance Banjarmasin - Halimatus Sa’diah; Husnurrofiq Husnurrofiq; Mursanto Mursanto (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2023)
This study aims to examine: (1) To find out whether employee work discipline partially affects the performance of PT. Mandala Multifinance Banjarmasin. (2) To find out whether the employee's work motivation partially affects the performance of employees of PT. Mandala Multifinance Banjarmasin. (3) To find out whether work discipline and employee motivation simultaneously affect the performance of PT. Mandala Multifinance Banjarmasin. This research uses quantitative methods and is a type of survey research. Data collection techniques using a questionnaire in the form of a questionnaire. The number of respondents is 34 people with Multiple Linear Regression analysis. The results showed: (1) Work discipline and work motivation have a significant influence on employee performance at PT. Mandala Multifinance Banjarmasin. (2) Work discipline has no significant effect on employee performance at PT. Mandala Multifinance Banjarmasin. (3) Work motivation has a significant influence on employee performance at PT. Mandala Multifinance Banjarmasin.